Surface instability of a semi-infinite isotropic laminated plate under surface van der Waals forces - Wang, X.; Xu, Y.; Zhou, K. (Archives of Mechanics, 2015)
By means of complex variable method, the present work demonstrates that the surface of a semi-infinite isotropic laminated plate that is being attracted to a rigid contactor through van der Waals forces is always unstable. Two distinct surface instability modes are identified, and their wavenumbers and wavelengths are presented in concise and simple expressions. Furthermore, the two wavenumbers and wavelengths are completely determined by three elastic parameters of the laminated plate, three parameters related to the interactions between the surface and the contactor, and three parameters related to surface energy.